In-vitro Antioxidant and Wound Healing Properties of Combretum dolichopetalum Engl. & Diels (Combretaceae) - Victor Yao Atsu Barku, Alex Boye, Francis Erzah, Prince Tsamenyi (Journal of Applied Pharmaceutical Science, 2016)
Combretum dolichopetalum Engl. & Diels (Combretaceae) is a medicinal plant used in the Kpando Traditional Area for treating wounds. However, it has received little attention by the scientific world. The study was designed to evaluate the wound healing potential and antioxidant activities of the plant to confirm its folkloric use. Excision wound model was used with Penicillin as the standard reference drug. Sensitivity test was carried out on the extract against Staphylococcus aureus, Escherichia coli and Klebsiella pneumonia using disc diffusion method. The antioxidant activity was measured by three different spectrophotometric assays. The content of total phenolics and total flavonoids were also determined. The extract significantly caused wound healing and reduced microbial load. Similarly, the methanol extract significantly inhibited the growth of S. aureus and K. pneumonia at higher doses. Almost all results from the antioxidant activity models were concentration dependent with no significant difference from the standard Ascorbic acid except at very low concentrations. Tannins and flavonoids were present whose synergistic effects may be responsible for the high antioxidant activity. Correlation analysis between the values of DPPH and TAC (r2=0.7790) indicates the viability of the two models for evaluating antioxidants from medicinal plants.
Keywords: Antioxidant activity, wound healing, sensitivity test, free radicals.